Dystocia Due to Conjoined Twin Fetal Monster in a Murrah Buffalo: A Case Report - Singh, V.; Kumar, A.; Gupta, R. K.; Sachan, V.; Saxena , A. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
A malformation in the fetus may result into monstrosity which can result in difficult parturition. Fetal anomalies and monstrosities are common causes of dystocia in bovine (Shukla et al., 2007) with the incidence of 7.9 % in river buffaloes (Phogat et al., 1992). Dicephalus monsters have been reported in buffaloes (Srivastava et al., 2008) and cows (Chandrahasan et al., 2003). The present case report describes a rare condition of conjoined twins (dicephalus dipus dibrachius dicaudatus monster) causing dystocia and its successful obstetrical management in a Murrah buffalo.